ANTIFUNGAL ACTIVITIES OF HONEY AND ACACIA NILOTICA EXTRACTS (FUDMA JOURNAL OF SCIENCES, 2022)
The increasing threat of fungal resistant to current antifungal agents underscores the need for an alternative source of antifungal agents. This study was designed to investigate the antifungal activity of honey and Acacia nilotica extracts against four important fungal pathogens (Candida albican, Aspergillus niger, Trychophyton rubrum and Trychophyton mentagrophyte). The in vitro antifungal activity of honey, ethanolic leaves and stem-bark extracts from Acacia nilotica L was studied using agar well diffusion and micro broth dilution techniques. The honey and ethanolic crude leaf extract exhibited considerable fungistatic activity against the four fungal isolates. The maximum diameter zones of inhibition of 18.50 mm was observed in Candida albican with ethanolic leaves extracts while a minimum of 16.00 mm diameter zones of inhibition was found on Trychophyton rubrum and Trychophyton mentagrophyte. There was no activity against all the fungal isolates when ethanolic stem-bark extract was used. A maximum diameter zones of inhibition of 20.00 mm diameter was observed in Trychophyton rubrum with 50 %v/v of honey concentration, while a minimum 13.50 mm diameter zone of inhibition was found in Trychophyton mentagrophyte. The MIC and MFC of the extract against the fungal isolates ranged from 15.63 - 250.00 mg/ml and 31.25 - 250.00mg/ml for ethanolic leaves extract, 6.25-50% and 12.5-50% for honey, 32-128.00Âµg/ml and 32 - 128.00 Âµg/ml for fluconazole respectively. The in vitro antifungal activity revealed a considerable antifungal activity of honey and ethanolic leaves extracts of A. nilotica L. than stem-bark extract
Keywords: Acacia nilotica, Honey, Antifungal activity, ethanolic leaves